Responsibility in supply chains: Germany's due diligence act is a good start - Günther Maihold; Melanie Müller; Christina Saulich; Svenja Schöneich (Stiftung Wissenschaft und Politik (SWP), 2021)
On 3 March, the Federal Cabinet adopted an act on corporate due diligence in supply chains. This represents an important step towards German businesses assuming full and proper responsibility for the supply chains associated with their goods and services. The move puts Germany in a group of European countries like France and the Netherlands that have already instituted legal frameworks of their own. However, by choosing to exclude civil liability the German government has left aside a powerful tool for applying targeted pressure to companies that fail to fulfil their obligations. In order to maximise the law's impact, the German Bundestag and government should therefore adopt additional flanking measures. At the European and international levels, Germany can also contribute to making companies assume greater responsibility for their own supply chains.
Keywords: 320